Development and assimilate partition in Phaseolus vulgaris as a function of three light levels and three nitrogen doses - Almeida, Alex A. F. de; Lopes, Nei F.; Oliva, Marco A.; Barros, Raimundo S. (Pesquisa Agropecuaria Brasileira, 2014)
Growth, morphology, assimilate partition and dry matter production were studied in Phaseolus vulgaris L. cv. Negrito 897, under field conditions, at three light levels (30%, 70% and 100% of sunlight) and three nitrogen doses (zero, 30 and 60 kg of N/ha). Light flux densities and nitrogen levels induced modifications on the pattern of assimilate distribution, changing the growth and morphology of the plant. Solar energy reduction associated to an increase in nitrogen levels increased stem elongation and leaf area. Shoot/root ratio increased with shading and/or increment of nitrogen levels, changing the normal assimilate partition among organs, and proportionally, less amount of assimilate was exported to roots. However, the preferential sink sequence was not changed by treatments. The rate of dry matter production of the whole plant and its parts decreased with decreasing nitrogen levels and/or shading. A significant interaction between light and nitrogen on one hand and number and dry weight of the seeds on the other was observed. Reduction in light levels decreased the shoot temperature and, probably, delayed the senescence of the plant parts as a consequence of shading.